2016
DOI: 10.3390/f7080177
|View full text |Cite
|
Sign up to set email alerts
|

Diameter Growth, Biological Rotation Age and Biomass of Chinese Fir in Burning and Clearing Site Preparations in Subtropical China

Abstract: Sustained forest management of Cunninghamia lanceolata (Chinese fir) plantations in subtropical China is restricted by the limited availability of quantitative data. This study combines inventory data and tree-ring analysis of Chinese fir from natural and plantation forests that were subjected to controlled burning or brush clearing site preparations. Inter-annual variation of Chinese fir tree-ring widths were measured for the controlled burning, brush clearing and natural forest sites. The mean annual diametr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…The biomass of fast-growing Eucalyptus increased fast as the nutrients were relatively abundant at the early stage. That prescribed burning increased tree biomass C storage to some extent in Eucalyptus plantations in the present study was consistent with that observed in Chinese fir plantations by Zhou et al (2016).…”
Section: Discussionsupporting
confidence: 92%
“…The biomass of fast-growing Eucalyptus increased fast as the nutrients were relatively abundant at the early stage. That prescribed burning increased tree biomass C storage to some extent in Eucalyptus plantations in the present study was consistent with that observed in Chinese fir plantations by Zhou et al (2016).…”
Section: Discussionsupporting
confidence: 92%
“…Aboveground vegetation is one of the primary sources of the soil nitrogen pool, and plant species affect nitrogen mineralization rates [64]. Some studies have shown that thinning increased the composition and biomass of the understory [47,65], which subsequently altered litter decomposition and nutrient status, and enhanced nitrogen input into soil [66]. Similarly, in the present study, we found that understory vegetation biomass, forest floor biomass, and nitrogen concentration associated with the thinning intensity had a positive correlation with soil nitrogen concentration (Table A1).…”
Section: Wsa Changementioning
confidence: 99%
“…Chinese fir is native to China, Northern Vietnam, and Laos, and is one of the most important timber species in Southern China [46]. Chinese fir is a fast-growing tree species that accounts for 16% of all plantations in China, covering approximately 12 million ha [47]. A number of studies have mainly focused on Chinese fir growth and timber production [46,48,49].…”
Section: Introductionmentioning
confidence: 99%
“…It has been developed into a representative conifer and broadleaf mixed forest because a few natural broadleaf tree species (mentioned above) were reserved (ca. 10% of the initial aboveground biomass [48]) after cutting. The single-species forest (Sin) was completely cleared before 1988 and planted with Chinese fir in the late 1980s.…”
Section: Research Sitementioning
confidence: 99%
“…After the initial planting, a forest tending approach was implemented for 1 and 5 years. More supporting information on tree species composition, stand structure, hydrological characteristics, and soil parameters can be found in previous publications conducted at the same research site [37,48,49]. Meteorological data (air temperature, maximum air temperature, minimum air temperature, and precipitation) measured by a ground meteorological station ( Figure 1) were available to inform the calculation of the correlation with stand aboveground productivities.…”
Section: Research Sitementioning
confidence: 99%